SONOMETRIC MONITORING IN THE SCHOOL ENVIRONMENT: AN EXPERIMENTAL APPROACH THROUGH ELECTRONIC PROTOTYPING IN FULL-TIME EDUCATION - Alves, Rodrigo Henrique Risso Aires; Pereira, Mariana Arinana Canuto; Araújo, Estephanie Guimarães; Martins, Wilson Ramos; da Silva, Diana Lima; dos Santos, Miquele Araújo; Oliveira, Ludimila Souza; Ponce, Ana Paula Silva (Seven Editora, 2026)
Noise pollution in the school environment is often neglected within extended school hours. This study analyzed the development of an automated technological artifact for measuring sound pressure levels, based on the Arduino platform, to integrate hearing comfort with digital instrumentation. Qualitative action research was conducted at the Integrated Center for Complementary Activities (CIAC) in Humaitá, Amazonas, as part of the "Science Workshop: Environmental Education and Sustainability" with Elementary School students. The application of maker culture and programming logic allowed students to technically diagnose the acoustic environment of their classrooms. Real-time decoding of sound data fostered critical thinking about public health and school ergonomics within the Amazonian reality, showing that the symbiosis between environmental education and technological practice enhanced the full-time curriculum and promoted the epistemological emancipation of the student.